A study of the effect of hemorrhage on the cardiorespiratory actions of halothane, isoflurane and sevoflurane in the dog - Teixeira Neto, Francisco José [UNESP]; Luna, Stélio Pacca Loureiro [UNESP]; Cruz, Mariangela L.; Braz, Jose R. C.; Massone, Flavio; Nogueira, Constanza S. (Blackwell Publishing, 2007)
Objective To compare the cardiorespiratory changes induced by equipotent concentrations of halothane (HAL), isoflurane (ISO) and sevollurane (SEVO) before and after hemorrhage.Study design. Prospective, randomized clinical trial.Animals. Twenty-four healthy adult dogs weighing 15.4 +/- 3.4 kg (mean +/- SD).Methods. Animals were randomly allocated to one of three groups (n = 8 per group). In each group, anesthesia was maintained with 1.5 minimum alveolar concentration of HAL (1.3%), ISO (1.9%,) and SEVO (3.5%) in oxygen. Controlled ventilation was performed to maintain eucapnia. Cardiorespiratory variables were evaluated at baseline (between 60 and 90 minutes after induction), immediately after and 30 minutes after the withdrawal of 32 mL kg(-1) of blood (400% of the estimated blood volume) over a 30-minute period.Results. During baseline conditions, ISO and SEVO resulted in higher cardiac index (CI) than HAL. Heart rates were higher with SEVO at baseline. while mean arterial pressure (MAP) and mean pulmonary arterial pressure did not differ between groups. Although heart rate values were higher for ISO and SEVO after hemorrhage, only ISO resulted in a higher CI when compared with HAL. In ISO-anesthetized dogs, MAP was higher immediately after hemorrhage, and this was related to better maintenance of CI and to an increase in systemic vascular resistance index from baseline.Conclusions. Although the hemodynamic responses of ISO and SEVO are similar in normovolaemic dogs, ISO results in better maintenance of circulatory function during the early period following a massive blood loss. Clinical relevance Inhaled anesthetics should be used judiciously in animals presented with blood loss. However, if an inhalational agent is to be used under these circumstances, ISO may provide better hemodynamic stability than SEVO or HAL.
Keywords: halothane; hemorrhage; isoflurane; sevoflurane; shock